Genome-wide identification and characterization of nucleotide binding site leucine-rich repeat genes in linseed reveal distinct patterns of gene structure - Kale, Sandip M.; Pardeshi, Varsha C.; Barvkar, Vitthal T.; Gupta, Vidya S.; Kadoo, Narendra Y. (Genome, 2013)
Plants employ different disease-resistance genes to detect pathogens and to induce defense responses. The largest class of these genes encodes proteins with nucleotide binding site (NBS) and leucine-rich repeat (LRR) domains. To identify the putative NBS-LRR encoding genes from linseed, we analyzed the recently published linseed genome sequence and identified 147 NBS-LRR genes. The NBS domain was used for phylogeny construction and these genes were classified into two well-known families, non-TIR (CNL) and TIR related (TNL), and formed eight clades in the neighbor-joining bootstrap tree. Eight different gene structures were observed among these genes. An unusual domain arrangement was observed in the TNL family members, predominantly in the TNL-5 clade members belonging to class D. About 12% of the genes observed were linseed specific. The study indicated that the linseed genes probably have an ancient origin with few progenitor genes. Quantitative expression analysis of five genes showed inducible expression. The in silico expression evidence was obtained for a few of these genes, and the expression was not correlated with the presence of any particular regulatory element or with unusual domain arrangement in those genes. This study will help in understanding the evolution of these genes, the development of disease resistant varieties, and the mechanism of disease resistance in linseed.
Keywords: Flax; in silico gene expression; motif analysis; NBS-LRR; Phylogenetic analysis; Promoter analysis

Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability

Distinct molecular features facilitating ice-binding mechanisms in hyperactive antifreeze proteins closely related to an Antarctic sea ice bacterium - Banerjee, Rachana; Chakraborti, Pratim; Bhowmick, Rupa; Mukhopadhyay, Subhasish (Journal of Biomolecular Structure & Dynamics, 2015)
Antifreeze proteins or ice-binding proteins (IBPs) facilitate the survival of certain cellular organisms in freezing environment by inhibiting the growth of ice crystals in solution. Present study identifies orthologs of the IBP of Colwellia sp. SLW05, which were obtained from a wide range of taxa. Phylogenetic analysis on the basis of conserved regions (predicted as the `ice-binding domain' [IBD]) present in all the orthologs, separates the bacterial and archaeal orthologs from that of the eukaryotes'. Correspondence analysis pointed out that the bacterial and archaeal IBDs have relatively higher average hydrophobicity than the eukaryotic members. IBDs belonging to bacterial as well as archaeal AFPs contain comparatively more strands, and therefore are revealed to be under higher evolutionary selection pressure. Molecular docking studies prove that the ice crystals form more stable complex with the bacterial as well as archaeal proteins than the eukaryotic orthologs. Analysis of the docked structures have traced out the ice-binding sites (IBSs) in all the orthologs which continue to facilitate ice-binding activity even after getting mutated with respect to the well-studied IBSs of Typhula ishikariensis and notably, all these mutations performing ice-binding using `anchored clathrate mechanism' have been found to prefer polar and hydrophilic amino acids. Horizontal gene transfer studies point toward a strong selection pressure favoring independent evolution of the IBPs in some polar organisms including prokaryotes as well as eukaryotes because these proteins facilitate the polar organisms to acclimatize to the adversities in their niche, thus safeguarding their existence.
Keywords: antifreeze proteins; horizontal gene transfer; ice-recrystallization inhibition; Molecular docking; Phylogenetic analysis